The effect of human resources competency, individual morality and the control environment on village government accountability in managing village fund allocation in Kupang Tengah District, Kupang District - Kerihi, Anthon Simon Yohanis (Goodwood Publishing, 2024)
Purpose: This study aims to analyze the influence of human resource competence, individual morality, and the control environment on the accountability of village governments in managing the allocation of village funds. Method: The study used purposive non-probability sampling with 35 village officials from seven villages in the Central Kupang District. Data were collected using a Likert scale and analyzed using a descriptive-quantitative approach with multiple linear regression in SPSS 25. Results: The results show that human resource competence, individual morality, and the control environment significantly affect village government accountability in managing fund allocations. Simultaneously, their combined influence reached 66.2%, indicating that these factors enhance accountability in the Central Kupang District. Conclusion: The study concludes that strengthening human resource capacity, fostering moral integrity, and ensuring a sound control environment are critical for improving accountability in village fund management. Limitation: This research is limited to a small sample of seven villages in one district; therefore, the results may not fully represent other regions or broader governance contexts. Contribution: This study contributes to the literature on public sector accountability by providing empirical evidence from the village government. It also offers practical insights for policymakers to strengthen governance through capacity building, ethical orientation, and effective internal control systems.